THE MICROORGANISMS COMMUNITIES IN THE SOIL UNDER THE CULTIVATION OF CARROT (Daucus carota L.) - Elżbieta Patkowska; Marzena Błażewicz-Woźniak (Acta Scientiarum Polonorum: Hortorum Cultus, 2014)
The composition of populations of soil microorganisms depends on a number of factors, for example the species of intercrop ground cover plants. The purpose of the studies was to determine the quantitative and qualitative composition of the populations of soil microorganisms in the cultivation of carrot considering different manners of soil cultivation and with the use of oat, spring vetch and tansy phacelia as intercrop ground cover crops. The greatest population of total bacteria occurred in the soil where oat was the ground cover plants. The most of total fungi was observed in the control. The application of ground cover plants contributed to an increased number of antagonistic Bacillus spp., Pseudomonas spp., Gliocladium spp., Penicillium spp. and Trichoderma spp. The tillage system had no significant effect on the population of microorganisms in the soil.